2021
DOI: 10.3390/ijerph18052365
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Conservative Treatment According to Severity and Systemic Disease in Carpal Tunnel Syndrome: A Systematic Review

Abstract: (1) Background: Carpal tunnel syndrome (CTS) is the most common peripheral neuropathy in the upper extremity. Conservative treatment has been effective for mild and moderate idiopathic CTS. However, severe CTS and systemic conditions were an exclusion criterion from the studies. The aim of this study is to review the effectiveness of conservative treatment in patients with CTS regardless of the level of severity and the presence or not of systemic diseases in the last ten years. (2) Methods: Randomized control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 61 publications
1
17
0
1
Order By: Relevance
“…The results of this meta-analysis are consistent with the previous systematic reviews that showed positive effects after manual therapy treatment on symptoms and function in patients with CTS [ 21 , 29 , 31 33 ]. In these reviews, the intervention included all conservative treatments, whereas in this meta-analysis, the effect of manual therapy interventions in isolation was analyzed.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this meta-analysis are consistent with the previous systematic reviews that showed positive effects after manual therapy treatment on symptoms and function in patients with CTS [ 21 , 29 , 31 33 ]. In these reviews, the intervention included all conservative treatments, whereas in this meta-analysis, the effect of manual therapy interventions in isolation was analyzed.…”
Section: Discussionsupporting
confidence: 90%
“…The number of studies analyzing manual therapy interventions has increased in last years, and they have shown positive effects on symptoms and physical function in patients with CTS [14][15][16][17][18][19][20]. Although a recent review has assessed the effects of conservative treatments in patients with CTS [21], to the best of our knowledge, no systematic review with meta-analysis has been performed in order to assess the effectiveness of manual therapy on the main symptoms, function, and nerve conduction studies in patients with CTS [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Tatalaksana CTS diberikan berdasarkan beratnya penyakit. Pada kasus ringan dan sedang, direkomendasikan terapi konservatif (8). Penderita CTS berat atau kerusakan saraf pada pemeriksaan elektrodiagnostik dilakukan pembedahan dekompresi.…”
Section: Pendahuluanunclassified
“…Other factors, for example, age, hereditary, and anthropometric components, have been implicated in the risk factors of idiopathic CTS [ 10 ]. Obesity, diabetes, and hypothyroidism have been associated with a double chance of developing CTS due to increased intraneural pressure in the carpal tunnel or vascular deficits [ 11 ].…”
Section: Introductionmentioning
confidence: 99%